A multi-sensor sub-Nyquist power spectrum blind sampling approach for low-power wireless sensors in operational modal analysis applications. (1st February 2019) - Gkoktsi, Kyriaki; Giaralis, Agathoklis
Highlights: Sub-Nyquist spectral estimation is developed for multi-sensor modal identification. Mode shapes are estimated from signals sampled at up to 89% below Nyquist rate. No prior knowledge of signal spectral content/sparsity is required. Up to 5 times sensor battery life extension through multi-coset compressive sampling. Abstract: A novel power spectrum blind sampling (PSBS) approach is proposed supporting low-power wireless sensor networks for Operational Modal Analysis (OMA) applications. The developed approach relies on sensors, employing deterministic non-uniform in time multi-coset sampling to acquire structural response acceleration signals at sub-Nyquist sampling rates. These signals are treated as realizations of stationary random processes without making any assumption about the average signal frequency content and spectral support. The acquired compressed measurements are transmitted to a central server and collectively processed via a PSBS technique, herein extended to the multi-sensor case, to estimate the power spectral density matrix of an underlying spatially correlated stationary response acceleration random process directly from the compressed measurements. Structural modal properties are then extracted through standard frequency domain decomposition (FDD). The efficacy of the proposed approach to resolve closely-spaced modes is numerically tested for various data compression levels using noisy response acceleration signals of a white-noise excited finite element model of a space truss as well as field-recorded acceleration time-histories of an instrumented bridge under operational loading. It is shown that accurate mode shapes based on the modal assurance criterion can be obtained from as low as 89% less measurements compared to conventional non-compressive FDD at Nyquist sampling rate. Further, significant gains in energy consumption and 3 to 5 times battery life extension are estimated for wireless sensors operating on multi-coset sampling at different data compression levels. It is, therefore, concluded that the proposed PSBS approach could provide long-term structural health monitoring systems with low-maintenance cost once wireless sensors with multi-coset sampling capabilities become commercially available.